Benign synthesis of unsymmetrical arylurea derivatives using 3-substituted dioxazolones as isocyanate surrogates. Issue 3 (2nd July 2020) - Chamni, Supakarn; Zhang, Jinquan; Zou, Hongbin
ABSTRACT: A phosgene- and metal-free synthesis of unsymmetrical arylurea derivatives utilizing 3-substituted dioxazolones and commercially available amines has been developed. The 3-substituted dioxazolones serve as the precursors of the in situ generated isocyanate intermediates in the presence of non-toxic sodium acetate as a base and methanol as a solvent under mild heating conditions. A series of unsymmetrical phenylureas including N, N' - mono-, di-, and trisubstituted derivatives are chemoselectively obtained in moderate to excellent yields from a broad scope of both 3-substituted dioxazolones and amines without a significant amount of the symmetrical byproducts. In many cases, the resulting unsymmetrical phenylureas are easily separated by filtration allowing no chromatographic purification. These investigations provide an opportunity for facile, practical, and eco-friendly synthesis of unsymmetrical diarylureas. Application of this method is demonstrated toward the gram-scale preparation of anti-cancer drugs, sorafenib and the 3-cycle continuous synthesis in conjugation with the recycle of sodium acetate and methanol process of known herbicide, daimuron. GRAPHICAL ABSTRACT: